Overview of Students' Academic Stress Levels on Online Learning During the Covid-19 Pandemic - Cucu Rokayah; Eli Fitri Sholihah; Fitra Herdian (GLOBAL HEALTH SCIENCE GROUP, 2022)
The COVID-19 pandemic has made the shift from education to online learning. These changes trigger academic stress. This study aims to determine the Description of Academic Stress Levels of Students of Diploma Nursing Institute to Online Learning During the Covid-19 Pandemic. This type of research is descriptive quantitative with a cross-sectional approach. This research was conducted in July 2021 with a population of 154 students. The sampling method used the Slovin formula with proportional random sampling technique so that the number of samples obtained was 111 students. Data retrieval using an academic stress questionnaire distributed in the form of google form. Data analysis used univariate analysis. The results showed that the Diploma of Nursing students experienced moderate stress (75%) due to poorly understood material, difficulty concentrating, and many distractions when studying at home. To cope with stress, students can do fun activities, increase worship, relax, exercise, express complaints to those closest to them and apply a healthy lifestyle.